Economic Benefit Analysis of Sorghum Crop Aid for Farmers in Tinondo District, East Kolaka Regency - Arya Fadjar Pratama; Surni; Samsul Alam Fyka (International Journal of Technology and Education Research, 2025)
This research is based on the fact that there are still many people who have not cultivated sorghum plants. In fact, sorghum plants are among the easiest carbohydrate-producing plants to cultivate.Sorghum has great potential to be developed in Indonesia because it has broad adaptability, especially on dry land and produces quite high productivity. Sorghum has characteristics that are closer to wheat, so it has the potential to replace wheat and can produce sugar.The aim of this research is to find out the reasons why farmers receive sorghum crop assistance from the government in Tinondo District, East Kolaka Regency and to find out the economic benefits of sorghum plants on the income of sorghum farmers in Tinondo District, East Kolaka Regency.The data used was primary data sourced from questionnaires distributed to respondents and secondary data from related agencies, literature and reports or results of previous research. The research method used was a qualitative and quantitative research method used analysis of farming income and the R/C ratio. The research results showed that the reasons why farmers received sorghum plant assistance from the Government in Tinondo District, East Kolaka Regency were that the soil conditions were suitable for planting sorghum, there was a lot of vacant land in the community, farmers did not need to buy sorghum seeds, the quality of the seeds was good, maintenance costs were cheap, and the plants Sorghum is more profitable than corn. The R/C value for total costs is 1.68 and the results of the income analysis of sorghum farming can be said clearly that sorghum farming is very profitable to run